Effects and optimization of pilot sequence length on rate in multiuser massive MIMO FDD system - Yi WANG; Pengge MA; Kaizhi HUANG; Chunguo LI; Yongming HUANG; Lyuxi YANG (Tongxin xuebao)
The effect of pilot sequence length on the asymptotic performance of the ergodic rate was investigated for the multiuser massive multiple-input multiple-output (MIMO) frequency division duplexing (FDD) downlink system.Firstly,the analytical expression of the ergodic rate was derived by using the principle of deterministic equivalence,based on which,it was discovered from the analytical results in two-fold that the normalized pilot sequence length (defined as the pilot sequence length divided by the number of BS antennas) tends to zero yet the rate was guaranteed to grow large without limit as long as the BS antenna number continues to increase,the rate saturates to a certain level if the BS antenna number becomes large with fixed pilot sequence length.Moreover,the pilot sequence length was optimized based on the sum-rate maximization within a finite channel coherence time,and a closed-form solution was deduced under a special correlated channel by means of Lambert W function.Simulation results validate the correctness of the theoretical analysis results and verify the effectiveness of the proposed closed-form solution of the optimal pilot sequence length.